Humanized MISTRG as a preclinical in vivo model to study human neutrophil-mediated immune processes - Martinez-Sanz, Paula; Laurent, Adrien R. G.; Slot, Edith; Hoogenboezem, Mark; Bąbała, Nikolina; van Bruggen, Robin; Rongvaux, Anthony; Flavell, Richard A.; Tytgat, Godelieve A. M.; Franke, Katka; Matlung, Hanke L.; Kuijpers, Taco W.; et al. (Frontiers in Immunology, 2023)
MISTRG mice have been genetically modified to allow development of a human myeloid compartment from engrafted human CD34+ haemopoietic stem cells, making them particularly suited to study the human innate immune system in vivo. Here, we characterized the human neutrophil population in these mice to establish a model that can be used to study the biology and contribution in immune processes of these cells in vivo. We could isolate human bone marrow neutrophils from humanized MISTRG mice and confirmed that all neutrophil maturation stages from promyelocytes (CD11b–CD16–) to end-stage segmented cells (CD11b+CD16+) were present. We documented that these cells possessed normal functional properties, including degranulation, reactive oxygen species production, adhesion and antibody-dependent cellular cytotoxicity towards antibody-opsonized tumor cells ex vivo. The acquisition of functional capacities positively correlated with the maturation state of the cell. We found that human neutrophils were retained in the bone marrow of humanized MISTRG mice during steady state. However, the mature segmented CD11b+CD16+ human neutrophils were released from the bone marrow in response to two well-established neutrophil-mobilizing agents (i.e., G-CSF and/or CXCR4 antagonist Plerixafor). Moreover, the neutrophil population in the humanized MISTRG mice actively reacted to thioglycolate-induced peritonitis and could infiltrate implanted human tumors, as shown by flow cytometry and fluorescent microscopy, providing a model to study the various functions of neutrophils in inflammation and in tumors. These results show that functional human neutrophils are generated and can be studied in vivo using the MISTRG mouse model.